Comparison of thermal performances of plate-fin and pin-fin heat sinks subject to an impinging flow - Kim, Dong-Kwon; Kim, Sung Jin; Bae, Jin-Kwon (International journal of heat and mass transfer, 2009)
In this paper, we compare thermal performances of two types of heat sinks commonly used in the electronic equipment industry: plate-fin and pin-fin heat sinks. In particular, heat sinks subject to an impinging flow are considered. For comparison of the heat sinks, experimental investigations are performed for various flow rates and channel widths. From experimental data, we suggest a model based on the volume averaging approach for predicting the pressure drop and the thermal resistance. By using the model, thermal resistances of the optimized plate-fin and pin-fin heat sinks are compared. Finally, a contour map, which depicts the ratio of the thermal resistances of the optimized plate-fin and pin-fin heat sinks as a function of dimensionless pumping power and dimensionless length, is presented. The contour map indicates that optimized pin-fin heat sinks possess lower thermal resistances than optimized plate-fin heat sinks when dimensionless pumping power is small and the dimensionless length of heat sinks is large. On the contrary, the optimized plate-fin heat sinks have smaller thermal resistances when dimensionless pumping power is large and the dimensionless length of heat sinks is small.